Manufacturing method of lithium ion battery and lithium ion battery
By using the positive electrode precursor layer of lithium alloy particles and a positive electrode active material in the lithium-ion battery, the problem of the capacity of the lithium-ion battery decreases during initial charging and repeated charging and discharge is solved, and the cycle characteristics of the battery are significantly improved.
Patent Information
- Application Number
- CN202411356937.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-06
- Filing Date
- 2024-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
The capacity of the existing lithium-ion batteries is significantly reduced after initial charging, and the capacity is further reduced during repeated charging and discharge, and the cycle characteristics are poor.
A positive electrode precursor layer containing lithium alloy particles and positive electrode active material is used, and the positive electrode precursor layer becomes a positive electrode active material layer by initial charging. The lithium alloying potential of the lithium alloy particles is 0.5V (vsLi/Li+) or more, and D90 is 70 μm or less.
The capacity reduction after initial charging is effectively suppressed, and the capacity reduction is suppressed during repeated charging and discharge, improving the cycle characteristics of the battery.
Smart Images

Figure CN119786744A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for manufacturing a lithium ion battery and a lithium ion battery. Background Art
[0002] In the past, in order to increase the capacity of lithium-ion batteries, the active materials in lithium-ion batteries have been improved.
[0003] Japanese Patent Application Laid-Open No. 2014-010991 discloses an electrode for a non-aqueous electrolyte secondary battery. The specific surface area of the negative electrode active material of the electrode measured by a nitrogen adsorption method is 3.3 m 2 / g or more and 4.4m 2 / g or less. The DBP oil absorption of the positive electrode active material of the electrode is 30 ml / 100 g or more and 47 ml / 100 g or less. The positive electrode density is 1.8 g / cm 3 Above and 2.2g / cm 3 Japanese Patent Application Laid-Open No. 2014-010991 discloses that the capacity of a negative electrode can be increased by using a lithium (Li) alloy as an active material.
[0004] In addition, as a positive electrode active material, nickel cobalt manganese (NCM) lithium oxide is widely used as a positive electrode active material, and improvement of its composition has also been studied. Summary of the invention
[0005] When using conventional electrodes such as the electrode disclosed in Japanese Patent Application Laid-Open No. 2014-010991, a significant decrease in capacity may be observed after initial charging. In addition, batteries are also required to have good cycle characteristics, that is, to suppress a decrease in capacity when repeatedly charged and discharged.
[0006] Therefore, the present disclosure provides a new method for manufacturing a lithium ion battery and a lithium ion battery capable of suppressing a decrease in capacity after initial charge and suppressing a decrease in capacity when charge and discharge are repeated.
[0007] The present inventors have conducted intensive research and found that the above-mentioned problems can be solved by the following means, thereby completing the present disclosure. That is, the present disclosure is as follows:
[0008] <Method 1> A method for manufacturing a lithium ion battery, comprising: providing a positive electrode precursor layer containing at least lithium alloy particles and a positive electrode active material; providing a lithium ion battery precursor having the positive electrode precursor layer, a separator layer and a negative electrode active material layer in sequence and impregnated with an electrolyte; and initially charging the lithium ion battery precursor so that the positive electrode precursor layer becomes a positive electrode active material layer, wherein the lithium alloy particles have a lithium alloying potential of 0.5 V (vsLi / Li +, that is, relative to Li / Li + ) or more and having a D90 of 70 μm or less as measured by a laser diffraction scattering method.
[0009] <Aspect 2> The method for producing a lithium ion battery according to aspect 1, wherein the lithium alloy particles are selected from the group consisting of Li3Bi, Li3Sb and LiSn.
[0010] <Method 3> The method for producing a lithium ion battery according to Method 1 or 2, wherein the positive electrode active material is NCM lithium oxide.
[0011] <Method 4> A lithium ion battery, which has a positive electrode active material layer, a separator layer and a negative electrode active material layer in sequence, the positive electrode active material layer contains a positive electrode active material and at least one of bismuth single particle, antimony single particle and tin single particle, and the D90 of the bismuth single particle, antimony single particle and tin single particle measured by a laser diffraction scattering method is less than 70 μm.
[0012] According to the present disclosure, it is possible to provide a new method for manufacturing a lithium ion battery and a lithium ion battery capable of suppressing a decrease in capacity after initial charge and suppressing a decrease in capacity when charge and discharge are repeated. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention are described below with reference to the accompanying drawings, in which like reference numerals represent like elements, and in which:
[0014] Figure 1 is a schematic diagram of a lithium ion battery of the present invention. DETAILED DESCRIPTION
[0015] Method for manufacturing lithium-ion battery
[0016] The method for manufacturing a lithium ion battery disclosed in the present invention comprises: providing a positive electrode precursor layer containing at least lithium alloy particles and a positive electrode active material; obtaining a lithium ion battery precursor having the positive electrode precursor layer, a separator layer and a negative electrode active material layer in sequence and impregnated with an electrolyte; and initially charging the lithium ion battery precursor so that the positive electrode precursor layer becomes a positive electrode active material layer, wherein the lithium alloy particles have a lithium alloying potential of 0.5V (vsLi / Li + ) or more and having a D90 of 70 μm or less as measured by a laser diffraction scattering method.
[0017] The inventors of the present disclosure have found that the reason for the capacity reduction described in Japanese Patent Application Laid-Open No. 2014-010991 is that a solid electrolyte interphase (SEI) is formed in the negative electrode during initial charge, thereby consuming Li provided in the initial positive electrode active material.
[0018] In contrast, the inventors of the present disclosure have found that the capacity of a lithium-ion battery can be improved by using the above-mentioned positive electrode precursor layer. Without being bound by theory, it can be considered that this is because the lithium in the lithium alloy particles in the positive electrode precursor layer is released during the initial charge and becomes lithium consumed to form SEI in the negative electrode, thereby suppressing the lithium in the positive electrode active material from being consumed to form SEI. In addition, it can be considered that by making the lithium alloying potential of the lithium alloy particles 0.5V (vsLi / Li + ) or above, it is possible to suppress the electrochemical reaction inside the positive electrode precursor before the initial charge.
[0019] On the other hand, when lithium alloy particles are used, there is a problem of poor cycle characteristics. When repeated charge and discharge are performed, sometimes a small number of charge and discharge times will significantly reduce the capacity. The inventors have found that the reason is that the metal constituting the lithium alloy particles is oxidized and dissolved during charging to form a high concentration of metal ions locally. These ions are concentrated in one place in the negative electrode, thereby generating resistance.
[0020] In view of this, the present inventors have found that by using lithium alloy particles having a D90 of 70 μm, the concentrated precipitation of metal in the negative electrode can be suppressed, thereby solving the above-mentioned problem.
[0021] Hereinafter, each constituent element of the present disclosure will be described.
[0022] Fabrication of cathode precursor layer
[0023] The positive electrode precursor layer contains at least a lithium alloying potential of 0.5V (vsLi / Li + ) or more lithium alloy particles and positive electrode active materials. In addition, the positive electrode precursor layer may also contain other optional substances. As other substances, conductive additives and binders can be cited.
[0024] The positive electrode precursor layer can be prepared by mixing the various materials that constitute it and then coating it.
[0025] Lithium alloy particles
[0026] The lithium alloy particles have a lithium alloying potential of 0.5 V (vsLi / Li + ) or more and D90 is 70 μm or less.
[0027] The lithium alloying potential of the lithium alloy particles can be 0.6 V (vs Li / Li + ) or above, 0.7V(vsLi / Li + ) or above, or 0.8V(vsLi / Li + ) or more, and can be 1.5V (vsLi / Li + ) or less, 1.4V(vsLi / Li + ) or less, 1.3V(vsLi / Li + ) or less, 1.2V(vsLi / Li + ) or less, 1.1V(vsLi / Li + ) or less, 1.0V(vsLi / Li + )the following.
[0028] Among them, the lithium alloying potential (vsLi / Li + ) is the electrode potential of the electrode reaction of formula (1), expressed with reference to the electrode potential of lithium of the following formula (2):
[0029] x + +M+xe - ←→LixM(1)
[0030] Li + +e - ←→Li(2)
[0031] The lithium alloying potential (vsLi / Li + ) can be measured as the unipolar potential obtained when the alloy is immersed in a lithium salt solution.
[0032] The D90 of the lithium alloy particles is 70 μm or less. The D90 may be 65 μm or less, 60 μm or less, 55 μm or less, 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less. The D90 may be 5 μm or more, 10 μm or more, or 15 μm or more.
[0033] Particles having such a value of D90 can be obtained, for example, by allowing lithium alloy particles to pass through a sieve having a pore size within the above range.
[0034] D50 of the lithium alloy particles is not particularly limited as long as it satisfies the above-mentioned D90, and may be, for example, 1 μm or more, 3 μm or more, 5 μm or more, or 7 μm or less, or 60 μm or less, 55 μm or less, or 50 μm or less.
[0035] The above D90 and D50 respectively refer to the particle diameter (D90 diameter) at the cumulative value of 90% and the particle diameter (D50 diameter) at the cumulative value of 50% in the volume-based particle size distribution obtained by the laser diffraction scattering method.
[0036] As such lithium alloy particles, for example, Li3Bi, Li3Sb, LiSn, etc. can be used.
[0037] Positive electrode active material
[0038] As the positive electrode active material, optional positive electrode active materials can be used, and there is no particular limitation. For example, lithium-containing oxides can be used.
[0039] The lithium-containing oxide as the positive electrode active material is not particularly limited. For example, it can be a lithium-containing oxide containing at least Li, at least one transition metal element selected from Co, Ni, and Mn, and O. As such a lithium-containing oxide, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganate (LiMn2O4), and nickel cobalt manganese (NCM) lithium oxides in which a part of the elements of these lithium-containing oxides are replaced with other elements can be used. NCM lithium oxides are generally represented by the general formula Li a Mn x Ni y Co z O 2±δ (0 < a ≤ 1.5, 0 ≤ x ≤ 1.5, 0 ≤ y ≤ 1.5, 0 ≤ z ≤ 1.5, 0 ≤ δ(=x + y + z) < 1.5). For example, LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), etc. can be used. The lithium-containing oxide as the positive electrode active material can be, for example, a substance having an O2-type structure, a substance having an O3-type structure, or a substance having a crystal structure other than these. As the positive electrode active material, only one kind can be used alone, or two or more kinds can be used in combination.
[0040] Conductive additive
[0041] As the conductive additive optionally contained in the positive electrode precursor layer, substances known as conductive additives used in lithium ion batteries can be used. Specifically, carbon materials such as Ketjen black (KB), vapor grown carbon fiber (VGCF), acetylene black (AB), carbon nanotube (CNT), carbon nanofiber (CNF), carbon black, coke, graphite, etc. can be used. Alternatively, metal materials that can withstand the environment during battery use can also be used. As the conductive additive, only one kind can be used alone, or two or more kinds can be used in combination. The shape of the conductive additive can be various shapes such as powder shape and fiber shape. The amount of the conductive additive contained in the positive electrode active material layer is not particularly limited.
[0042] Adhesives
[0043] As the binder arbitrarily contained in the positive electrode precursor layer, a binder known as a binder used in a lithium ion battery can be used. For example, styrene-butadiene rubber (SBR) based binders, carboxymethyl cellulose (CMC) based binders, acrylonitrile-butadiene rubber (ABR) based binders, butadiene rubber (BR) based binders, polyvinylidene fluoride (PVDF) based binders, polytetrafluoroethylene (PTFE) based binders, etc. can be used. The binder can be used alone or in combination of two or more. The amount of the binder contained in the positive electrode active material layer is not particularly limited.
[0044] Preparation of Lithium-ion Battery Precursors
[0045] The lithium ion battery precursor has a positive electrode precursor layer, a separator layer and a negative electrode active material layer in order, and is impregnated with a non-aqueous electrolyte. The lithium ion battery precursor can be prepared by a known method.
[0046] In addition, the lithium ion battery precursor may further include a positive electrode current collector layer and a negative electrode current collector layer.
[0047] The components of the lithium-ion battery precursor are described below.
[0048] Positive electrode collector layer
[0049] The positive electrode collector layer can be composed of known metals that can be used as positive electrode collectors of lithium ion batteries. As such metals, metal materials containing at least one element selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Pb, Co, Cr, Zn, Ge, In, Sn, and Zr can be exemplified. The form of the positive electrode collector is not particularly limited. Various forms such as foil, mesh, and porous can be used. It can also be a substrate formed by vapor deposition or plating of the above metal on the surface of the substrate.
[0050] Diaphragm
[0051] As the separator, a separator known as a separator used in a lithium ion battery can be used. For example, the separator can be composed of resins such as polyethylene (PE), polypropylene (PP), polyester and polyamide. The separator can be a single-layer structure, or it can also be a multi-layer structure. As a multi-layer structure separator, for example, a multi-layer structure separator composed of the above resins can be used, such as a 2-layer structure separator of PE / PP, or a 3-layer structure separator of PP / PE / PP or PE / PP / PE. The separator can be composed of non-woven fabrics such as cellulose non-woven fabrics, resin non-woven fabrics, and glass fiber non-woven fabrics. The thickness of the separator is not particularly limited, for example, it can be 5 μm or more and 1 mm or less.
[0052] Negative electrode active material layer
[0053] The negative electrode active material layer contains the negative electrode active material. In addition, the negative electrode active material layer may contain other optional components. As other components, for example, a conductive aid and a binder can be cited. As the conductive aid and the binder, the description of the positive electrode active material layer can be referred to.
[0054] Negative electrode active material layer: Negative electrode active material
[0055] As the negative electrode active material, various materials whose potential for absorbing and releasing ions (charge and discharge potential) is lower than that of the positive electrode active material can be used. As the negative electrode active material, for example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite, lead or hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, etc. can be used. The negative electrode active material can be used alone or in combination of two or more.
[0056] Negative electrode collector layer
[0057] The negative electrode collector layer can be composed of known metals that can be used as negative electrode collectors of lithium ion batteries. As such a metal, for example, it can be a metal material containing at least one element selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Pb, Co, Cr, Zn, Ge, In, Sn, and Zr. The form of the negative electrode collector layer is not particularly limited, and can be various forms such as foil, mesh, and porous. The negative electrode collector layer can be a layer formed by plating or vapor-depositing the above-mentioned metal on the surface of a substrate composed of an optional material. In addition, the surface of the negative electrode collector layer can be covered with a carbon material or the like.
[0058] Non-aqueous electrolytes
[0059] The nonaqueous electrolyte may contain a nonaqueous solvent and an electrolyte. The electrolyte may contain alkali metal ions, such as lithium ions, as carrier ions.
[0060] The non-aqueous solvent can use a solvent other than water, such as an organic solvent. As the organic solvent, for example, carbonate solvents such as ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and fluoroethylene carbonate (FEC) can be used. These organic solvents can be used alone or in combination.
[0061] The electrolyte is not particularly limited, and may be, for example, a lithium salt. As the lithium salt, for example, LiPF6 or the like may be used.
[0062] Preparation of positive electrode active material layer
[0063] The positive electrode active material layer is prepared by initially charging the lithium ion battery precursor so that the positive electrode precursor layer becomes the positive electrode active material layer.
[0064] By initially charging the lithium ion battery precursor having the positive electrode precursor layer, the lithium of the lithium alloy particles is consumed, thereby forming SEI in the negative electrode. As a result, when the lithium alloy particles contain at least one of Li3Bi, Li3Sb and LiSn, the obtained positive electrode active material layer contains at least one of bismuth single substance particles, antimony single substance particles and tin single substance particles.
[0065] The conditions for initial charging may be known conditions.
[0066] Lithium-ion battery
[0067] The lithium ion battery disclosed herein comprises a positive electrode active material layer, a separator layer and a negative electrode active material layer, wherein the positive electrode active material layer contains a positive electrode active material and at least one of bismuth single particle, antimony single particle and tin single particle, and the D90 of the bismuth single particle, antimony single particle and tin single particle measured by a laser diffraction scattering method is less than 70 μm.
[0068] Figure 1 The structure of a lithium-ion battery 100 according to one embodiment of the present disclosure is schematically shown. Figure 1 As shown in the figure, the lithium ion battery 100 may include a positive electrode 10, a separator 20, and a negative electrode 30. In addition, the positive electrode 10 may include a positive electrode active material layer 11 and a positive electrode collector layer 12, and the negative electrode 30 may include a negative electrode active material layer 31 and a negative electrode collector layer 32. In this case, the positive electrode active material layer 11 may include the above-mentioned positive electrode active material. In addition, although not shown in the figure, an electrolyte may be included in the positive electrode active material layer 11 and the negative electrode active material layer 31.
[0069] In addition, bismuth single substance particles, antimony single substance particles and tin single substance particles are formed by releasing lithium with a small atomic weight from the above-mentioned lithium alloy particles. Therefore, it can be considered that the particle size of these particles is the same as that of the lithium alloy particles before the reaction, or slightly smaller. Therefore, it can be considered that the D90 and D50 of these particles are also the same as those of the lithium alloy particles before the reaction, or slightly smaller.
[0070] From the above viewpoints, regarding D90 and D50 of bismuth single-element particles, antimony single-element particles, and tin single-element particles, reference can be made to the description of lithium alloy particles.
[0071] For each structure of the lithium ion battery, the description of the production method can be referred to.
[0072] Although the present disclosure is specifically described through Examples and Comparative Examples, the present disclosure is not limited thereto.
[0073] Lithium-ion battery manufacturing
[0074] Embodiment 1:
[0075] Li3Bi powder as lithium alloy particles was sieved with a 60 μm sieve, and D90 and D50 of the Li3Bi powder that passed through the sieve were measured by laser diffraction scattering method.
[0076] 92.3 mg of LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (NCM811), 8.4 mg of the above-mentioned Li3Bi powder as lithium alloy particles, a conductive additive and a binder were mixed in NMP to prepare a slurry. The slurry was applied on an Al foil and dried to obtain a positive electrode precursor layer.
[0077] The obtained positive electrode precursor layer is placed opposite to a negative electrode active material layer containing graphite as an active material via a separator layer, vacuum dried, and then a non-aqueous electrolyte is added to obtain a lithium ion battery precursor.
[0078] Examples 2-9 and Reference Examples 1-6
[0079] The lithium ion battery precursors of Examples 2-9 and Reference Examples 1-6 were prepared under the same conditions as in Example 1, except that the content of the positive electrode active material and the type, preparation conditions and content of the lithium alloy particles were changed as shown in Table 1. "60 and 20" in Table 1 means that the following particles are used, that is, the particles that passed the 60μm sieve were further sieved with a 20μm sieve, but the particles that did not pass the 20μm sieve were used.
[0080] evaluate
[0081] Battery capacity during initial charge and discharge
[0082] Based on the mass of the positive electrode active material contained in the battery, a current value of 210 mA / g is defined as a 1C rate, 0.2C is used as the charge and discharge current value, and 0.03C is used as the termination current value, and CCCV charging and CCCV discharging are performed. The upper limit voltage during charging is 4.25 V, and the lower limit voltage during discharging is 2.50 V. The obtained CCCV discharge capacity is used as the capacity of the battery and as an evaluation index of the present invention.
[0083] Cycle characteristics
[0084] After measuring the capacity of the battery, a cycle test (CC charge and CC discharge, upper and lower voltage limits 3-4.25V, 0.3C rate) was carried out to determine the number of cycles until the CC discharge capacity reached 40% or less of the initial discharge capacity.
[0085] Table 1 shows the configurations and evaluation results of Examples and Comparative Examples.
[0086] Table 1
[0087]
[0088] As shown in Table 1, the lithium alloying potential was 0.5 V (vsLi / Li + ) or more and having a D90 of 70 μm or less as measured by a laser diffraction scattering method, the lithium ion battery of the embodiment can suppress the decrease in capacity when repeatedly charged and discharged.
[0089] In addition, Examples 7-9 have the same degree of D90 as Examples 1-3, but D50 is a larger value, but there is no significant difference in the cycle characteristics. Therefore, it can be seen that a smaller D90 has a greater impact on the cycle characteristics than a smaller D50.
Claims
1. A method for manufacturing a lithium ion battery, characterized in that: include: Providing a positive electrode precursor layer containing at least lithium alloy particles and a positive electrode active material; Providing a lithium ion battery precursor having the positive electrode precursor layer, the separator layer and the negative electrode active material layer in sequence and impregnated with an electrolyte; and Initially charging the lithium-ion battery precursor so that the positive electrode precursor layer becomes a positive electrode active material layer, The lithium alloy particles have a lithium alloying potential relative to Li / Li + Lithium alloy particles having a D90 of 70 μm or less as measured by a laser diffraction scattering method at 0.5 V or higher.
2. The method for manufacturing a lithium-ion battery according to claim 1, characterized in that: The lithium alloy particles are selected from the group consisting of Li3Bi, Li3Sb and LiSn.
3. The method for manufacturing a lithium ion battery according to claim 1 or 2, characterized in that: The positive electrode active material is NCM lithium oxide.
4. A lithium ion battery, characterized in that: The invention has a positive electrode active material layer, a separator layer and a negative electrode active material layer in sequence. The positive electrode active material layer contains a positive electrode active material and at least one of bismuth single substance particles, antimony single substance particles, and tin single substance particles, and The bismuth single substance particles, the antimony single substance particles, and the tin single substance particles have a D90 measured by a laser diffraction scattering method of 70 μm or less.
Citation Information
Patent Citations
Electrode, nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery manufacturing method
JP2014010991A